Feasibility study of temporary permanent pacemaker in patients with conduction block after TAVR - Chang, Sanshuai; Liu, Xinmin; Lu, Zhi-Nan; Yao, Jing; Yin, Chengqian; Wu, Wenhui; Yuan, Fei; Luo, Taiyang; Liu, Ran; Yan, Yunfeng; Zhang, Qian; Pu, Junzhou; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Limited data exist on the use of temporary permanent pacemaker (TPPM) to reduce unnecessary PPM in patients with high-degree atrioventricular block (HAVB) after transcatheter aortic valve replacement (TAVR). Objectives This study aims to determine the feasibility of TPPM in patients with HAVB after TAVR to provide prolonged pacing as a bridge. Materials and methods One hundred and eleven consecutive patients undergoing TAVR were screened from August 2021 to June 2022. Patients with HAVB eligible for PPM were included. TPPM were used in these patients instead of conventional temporary pacing or early PPM. Patients were followed up for 1 month. Holter and pacemaker interrogation were used to determine whether to implant PPM. Results Twenty one patients met the inclusion criteria for TPPM, of which 14 patients were third-degree AVB, 1 patient was second-degree AVB, 6 patients were first degree AVB with PR interval > 240 ms and LBBB with QRS duration > 150 ms. TPPM were placed on the 21 patients for 35 ± 7 days. Among 15 patients with HAVB, 26.7% of them (n = 4) recovered to sinus rhythm; 46.7% (n = 7) recovered to sinus rhythm with bundle branch block. The remains of 26.7% patients (n = 4) still had third-degree AVB and received PPM. For patients with first-degree AVB and LBBB, PR interval shortened to < 200 ms in all 6 patients and LBBB recovered in 2 patients. TPPM were successfully removed from all patients and no procedure-related adverse events occurred. Conclusion TPPM is reliable and safe in the small sample of patients with conduction block after TAVR to provide certain buffer time to distinguish whether a PPM is necessary. Future studies with larger sample are needed for further validation of the current results.